Poverty Dimensions (with Special Reference to Sri Lanka) - Srikanthan, R. (My University, 2013)
Over 1.3 billion people in developing countries live on 1.26 $ a day or less.Based on World Bank figures which are used for official global poverty statistics the number of people living below the international poverty line of 1.25 $ per day fell from 1.82 billion to 1.37 billion between 1990 and 2005.Expressing poverty as a percentage provides more favourable results due to rising population in the last few decades,particularly in the developing countries.In sub - Saharan Africa, for example poverty fell slightly from 58% to 51 % between 1990 and 2005. Similarly the efforts taken between 1990 and 2008 to reduce the number of poor people where highly successful and the amount of people living in poverty decreased by nearly half from 48 to 26 percent. According to the latest United Nations Report, however food prices are back on the rise causing an increase in global poverty for the first time in nearly two decades (United Nations 2010) Some special features have been identified by the researchers in relations to poverty within the last two three decades. They are  The wealth of new Millennium has tended to increase inequality rather than reduce poverty. UNDP (United Nations Development Programme) has reported that in 2009 richest 500 people in the world earned more than the poorest 416 million  The trend of migration in the developing countries particularly in Africa and Latin American world has raised the incidence of urban poverty in the slum zone of the world major cities.  Rural poverty rates as in India and Bangladesh are more the double than those in cities.  The most persisting poverty is found among the ethnic minorities expressing discrimination.For instance the minority groups in the Central African countries are more vulnerable than the major ethnic groups. In this paper and attempt is made to bring out some salient features of poverty with specific examples from Sri Lanka. Secondary data deride from several sources including United Nations Reports, World Bank Reports and household income and 62 expenditure survey, 2006-7, 2009-10 are applied to support the text in relevant sections with suitable diagrams